D-loop mutations in mitochondrial DNA are a risk factor for chemotherapy resistance in esophageal cancer - Takashi Harino; Koji Tanaka; Daisuke Motooka; Yasunori Masuike; Tsuyoshi Takahashi; Kotaro Yamashita; Takuro Saito; Kazuyoshi Yamamoto; Tomoki Makino; Yukinori Kurokawa; Kiyokazu Nakajima; Hidetoshi Eguchi; et al. (Scientific Reports)
Abstract Esophageal cancer is a highly aggressive disease, and acquired resistance to chemotherapy remains a significant hurdle in its treatment. mtDNA, crucial for cellular energy production, is prone to mutations at a higher rate than nuclear DNA. These mutations can accumulate and disrupt cellular function; however, mtDNA mutations induced by chemotherapy in esophageal cancer remain unexplored. We aimed to identify such mutations in esophageal cancer, pre- and post-chemotherapy, and explore the relationship between them and clinicopathological factors associated with chemotherapy resistance. We investigated mtDNA mutations in Human esophageal squamous cell carcinoma (ESCC) cancer cell lines (TE8 and TE11) and patient samples (27 pre- and post-chemotherapy, and 96 post-chemotherapy) using next-generation sequencing. Our analysis revealed a rise in mtDNA mutations following chemotherapy, particularly within the D-loop region. Moreover, mutations in a specific D-loop segment (hypervariable segment 1; HVS1) were associated with lower mtDNA copy number, poorer response to chemotherapy, and decreased five-year survival rates. These findings suggest that HVS1 mutations in mtDNA acquired after chemotherapy may contribute to treatment resistance and poorer clinical outcomes in patients with esophageal cancer. This study sheds light on the mechanisms of chemotherapy resistance and provides valuable insights for future research to overcome this challenge.